Nanomechanics of shape memory alloys - M. Karami; X. Chen (Materials Today Advances, 2021)
Shape memory alloy undergoing reversible martensitic transformation is an important class of metallic functional materials. In the past two decades, the development of shape memory alloys enables great advances in biomedical devices, microelectronics, and energy conversions. As the application scales of these devices get smaller and smaller, it is very critical to understand and tune the mechanical properties of shape memory alloys in nanoscale regime. While there are extensive reviews of shape memory alloys regarding their macroscopic properties, metallurgical treatments, and applications in the design of microdevices, their nanomechanics are not well summarized and thoroughly compared transversely among different experimental setups. This review provides an insight of the latest discoveries in nanomechanics of NiTi-based and Cu-based shape memory alloys, which sorts out the size effects, the deformation mechanisms, and the functional fatigue of the miniaturized samples in single-crystalline and polycrystalline formats.